Evaluation of Four Commercial Composts on Strawberry Plant Productivity and Soil Characteristics in California. (30th November 2016) - Lloyd, Margaret; Kluepfel, Daniel; Gordon, Thomas
ABSTRACT: Composts can have beneficial effects on strawberry production and these benefits can be dependent on the type of compost used. Four commercial composts were evaluated: cow manure, spent mushroom, yard trimmings, and vermicompost. The nutrient composition, abundance of fungi and bacteria, and microbial activity were determined. Five field trials assessed effects on plant growth, root development, soil microbial activity, nutrient availability, and yield during one growing season. Manure and mushroom compost significantly increased soil electrical conductivity levels to 9.9 ± 1.7 dS/m and 7.3 ± 0.8 dS/m, respectively. Manure, yard trimmings, and mushroom composts shifted soil pH toward optimal levels for up to 7 months. Mushroom compost had the greatest effect on soil nitrate, which was up to 32 mg/kg of soil higher than non-amended soil. Significant effects on yield were more likely to occur where environmental conditions and management practices were less than optimal or compost was not routinely added. Several factors important to plant production were significantly affected by compost: soil salinity, plant establishment, soil nitrate, production curves, soil microbial activity, and soil pH.